2011
DOI: 10.1111/j.1567-1364.2010.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Sfl2, a temperature-induced transcriptional regulator, is required for virulence in a murine gastrointestinal infection model

Abstract: Many transcriptional regulators play roles in morphogenesis of the human pathogen Candida albicans. Recently, Sfl2, a sequence homolog of C. albicans Sfl1, has been shown to be required for hyphal development. In this report, we show that, like Sfl1, Sfl2 could complement the phenotypes of the Saccharomyces cerevisiae sfl1 mutant, and green fluorescent protein-tagged Sfl2 localized in the nuclei of both yeast and hyphal cells in C. albicans, reflecting its role as a transcriptional regulator. In C. albicans, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 47 publications
(124 reference statements)
3
52
0
Order By: Relevance
“…On the other hand, we and others have shown that deletion of SFL2 impaired filamentation in response to different cues, whereas SFL2 overexpression promoted hyphal growth, even under non hyphae-stimulating conditions [39][40][41]. Noteworthy, an sfl2D/ sfl2D strain exhibited reduced damage in a reconstituted human oral epithelium model and displayed attenuated virulence in a mouse model of gastrointestinal colonization and dissemination model [39,40], indicating that Sfl2p also plays an important role in C. albicans pathogenesis. Similar to Sfl1p, an Sfl2p-GFP fusion localized to the nucleus, in line with a role in transcriptional regulation [39].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, we and others have shown that deletion of SFL2 impaired filamentation in response to different cues, whereas SFL2 overexpression promoted hyphal growth, even under non hyphae-stimulating conditions [39][40][41]. Noteworthy, an sfl2D/ sfl2D strain exhibited reduced damage in a reconstituted human oral epithelium model and displayed attenuated virulence in a mouse model of gastrointestinal colonization and dissemination model [39,40], indicating that Sfl2p also plays an important role in C. albicans pathogenesis. Similar to Sfl1p, an Sfl2p-GFP fusion localized to the nucleus, in line with a role in transcriptional regulation [39].…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, an sfl2D/ sfl2D strain exhibited reduced damage in a reconstituted human oral epithelium model and displayed attenuated virulence in a mouse model of gastrointestinal colonization and dissemination model [39,40], indicating that Sfl2p also plays an important role in C. albicans pathogenesis. Similar to Sfl1p, an Sfl2p-GFP fusion localized to the nucleus, in line with a role in transcriptional regulation [39].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations